PERKEMBANGAN INFRASTRUKTUR PENGISIAN BATERAI KENDARAAN LISTRIK DI INDONESIA - Dharmawan, I. P.; Kumara, I. N. S.; Budiastra, I. N. (Jurnal SPEKTRUM; Vol 8 No 3 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i03.p12, 2021)
The development of electric vehicles in Indonesia started after the issuance of Presidential Decree 55/2019 about battery-based eletric vehicles. The development of electric vehicles must be supported with the charging infrastructure so users do not experience problems in charging the vehicles and therefore more people will switch to electric vehicle. This paper discusses the current status of charging infrastructure for electric vehicle in Indonesia. Currently, there are several type of vehicle charging facilites consist of 7.000 public electric charging station or SPLU, 97 public electric vehicle charging station or SPKLU, 9 public electric vehicle battery exchange station or SPBKLU distributed across Sumatra, Java, Bali, NTB, Sulawsi and Kalimantan. In the case of Bali, there are 166 of SPLU, 5 of SPKLU, and there is no SPBKLU yet. The total accumulative energy consumed through the charging stations in Bali is 169.481 kWh. The figure is low due to lack of information about the charging station and the fact that the number of electric vehicles in Bali is still low.